2019
DOI: 10.4028/www.scientific.net/kem.821.512
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Performances of Green Engineered Cementitious Composites Incorporating Various Types of Sand

Abstract: This paper evaluates the mechanical performances of green engineered cementitious composites (ECC) by means of compressive strength and flexural behaviour. Green ECC made of cement, ground granulated blast-furnace slag (GGBS), river sand or recycled concrete fine (RCF), polypropylene (PP) fiber, water and superplasticizer (SP) was employed in this study. Compression test result implies that green ECC incorporating either sieved river sand or sieved RCF (below 600 μm) in series G60 and G70 exhibited greater com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 16 publications
(18 reference statements)
1
1
0
Order By: Relevance
“…Apparently, the control specimen demonstrates brittle behavior in which the plate specimen failed directly upon reaching its first cracking strength. This behavior is similar to normal concrete, as demonstrated in a study by Lee et al (2019b). For the control specimen, neither GGBS nor PVA fibers were incorporated in the cementitious matrix, and it consisted of only cement mortar.…”
Section: Flexural Behaviorsupporting
confidence: 77%
See 1 more Smart Citation
“…Apparently, the control specimen demonstrates brittle behavior in which the plate specimen failed directly upon reaching its first cracking strength. This behavior is similar to normal concrete, as demonstrated in a study by Lee et al (2019b). For the control specimen, neither GGBS nor PVA fibers were incorporated in the cementitious matrix, and it consisted of only cement mortar.…”
Section: Flexural Behaviorsupporting
confidence: 77%
“…There are few types of fibers commonly employed in ECC mixtures, and it is found that ECCs that contain polyvinyl alcohol (PVA) fibers have consistently exhibited excellent durability, greater mechanical properties as well as enhanced structural performances (Meng et al, 2017;Pakravan et al, 2018;Yang & Li, 2014). Some researchers explored the use of polypropylene (PP) fibers instead of PVA in the making of ECC, together with some of the locally available materials (Zhang et al, 2014;Zhang et al, 2015;Lee et al, 2018b;Lee et al, 2019a, Lee et al, 2019bZhu et al, 2020). In one of these studies, PP fibers of volume fractions 1.5%, 2.0%, and 2.5% were employed in ECC with GGBS to study the flexural strength and ductility (Lee et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%